Analysis of Economic Empowerment Strategies of Ar-Raudhatul Hasanah Islamic Boarding School Medan - Padillah, Fahmil; Yafiz, Muhammad; Harahap, Isnaini; Marliyah, Marliyah; Putro, Sampurno (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
The purpose of this study was to analyze the economic empowerment strategy of the Ar-Raudhatul Hasanah  Islamic boarding school through the boarding school-owned business entity (BUMP) in order to improve the economy. In this research method used is descriptive with a qualitative approach. The results of this study indicate that the role of BUMP not only has an impact on improving the economy for pesantren, but is able to make a major contribution to the students who are included in running each existing business unit. And the strategy that can be done in economic empowerment is to provide opportunities for students to develop their potential in doing business. Expanding the target market by opening a business outside the pesantren that seeks to produce as much as possible both in terms of goods and services to be marketed. In order to create advanced economic activities based on sharia principles